Microbiostratigraphy and Lithostratigraphy of the Upper Permian Dalan Formation in Kuh-E-Surmeh (Zagros Basin, Southwest Iran) - Rafiee, Pedram; Baghbani, Dariush; Aghanabati, Ali; Arian, Mehran (International Journal of Geography and Geology, 2015)
The objective of the present study is to perform Microbiostratigraphy and Lithostratigraphy of the Upper Permian Dalan Formation in Kuh-e-Surmeh (Zagros Basin). The Upper Permian Dalan Formation contains vast gas reservoirs in the southwest Iran and is composed of three Members: The Lower Dalan Member is Wordian to Capitanian in age; the Nar Member is latest Capitanian and the Upper Dalan Member corresponds to Wuchiapingian to Changhsingian. Lower and Upper Dalan Members include mainly limestone, dolomite and Nar member mostly consist of anhydrite and thin interlayer of dolomite toward the base. The biostratigraphic study allows individualizing Foraminifers from the Roadian to the Changhsingian (Middle to Late Permian). Based on the stratigraphic distributions of the Biostratigraphically significant fauna and flora the following 5 biozones and age determinations are proposed in the Upper Permian Dalan Formation: 1. Paraglobivalvulinoides septulifera zone (Changhsingian) 2. Paradagmarita zone (Changhsingian) 3. Shanita zone (Middle - Late Capitanian) 4. Schwagerina zone (Wordian - Middle Capitanian) 5. Neoendothyra zone (Roadian)